2019
DOI: 10.1021/acs.inorgchem.9b01414
|View full text |Cite
|
Sign up to set email alerts
|

Tetranuclear Au2Cu2 Clusters with Butterfly- and Planar-Shaped Metal Cores: Strong Rigidochromism Induced by Jahn–Teller Distortion in Two-Coordinated Gold(I) Centers

Abstract: Two tetranuclear Au 2 Cu 2 cluster complexes [Au 2 Cu 2 (μ-(PPh 2 ) 2 py) 2 (μ-OH)](PF 6 ) 3 , 2, and [Au 2 Cu 2 Cl 2 (μ-(PPh 2 ) 2 py) 2 ](OTf) 2 , 4, have been prepared by the reactions of precursor complexes [Au 2 (μ-(PPh 2 ) 2 py) 2 ](OTf) 2 , 1, and [Cu 2 (μ-(PPh 2 ) 2 py) 2 (μ-SMe 2 )(OTf) 2 ], 3, with [Cu(NCCH 3 ) 4 ]PF 6 and AuCl(SMe 2 ), respectively. The crystal structures of complexes 2 and 4 were determined by X-ray crystallography, indicating a butterfly-shaped Au 2 Cu 2 metal core for 2 and a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In the 19 F­{ 1 H} NMR spectrum of 4 , the resonances of the F atoms of the coordinated OTf ligands and the OTf counterion appeared as singlet signals at δ −78.7 and −78.6 ppm, respectively (Figure S6). The general pattern and characteristics of the 13 C­{ 1 H} NMR spectrum of 4 were similar to those previously obtained for the binuclear gold­(I) complex, 1 (OTf) 2 , and the Au 2 Cu 2 clusters 2 and 3 . The positive-ion mode electrospray ionization (ESI) mass spectra of 4 , 5 , and 6 revealed an intense signal at m / z 644 due to binuclear gold species [Au 2 (μ-(PPh 2 ) 2 py) 2 ] 2+ , indicating that these clusters are labile in the gas phase and undergo dissociation via rupturing the Ag–N and Au–Ag bonds.…”
Section: Results and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the 19 F­{ 1 H} NMR spectrum of 4 , the resonances of the F atoms of the coordinated OTf ligands and the OTf counterion appeared as singlet signals at δ −78.7 and −78.6 ppm, respectively (Figure S6). The general pattern and characteristics of the 13 C­{ 1 H} NMR spectrum of 4 were similar to those previously obtained for the binuclear gold­(I) complex, 1 (OTf) 2 , and the Au 2 Cu 2 clusters 2 and 3 . The positive-ion mode electrospray ionization (ESI) mass spectra of 4 , 5 , and 6 revealed an intense signal at m / z 644 due to binuclear gold species [Au 2 (μ-(PPh 2 ) 2 py) 2 ] 2+ , indicating that these clusters are labile in the gas phase and undergo dissociation via rupturing the Ag–N and Au–Ag bonds.…”
Section: Results and Discussionsupporting
confidence: 77%
“…Very recently, we reported the preparation of binuclear gold­(I) complex, [Au 2 (μ-(PPh 2 ) 2 py) 2 ]­(OTf) 2 , 1 (OTf) 2 , in which (PPh 2 ) 2 py = bis­(diphenylphosphino)­pyridine (Scheme ). Complex 1 (OTf) 2 contains two uncoordinated pyridyl groups and provides the possibility of the coordination of the pyridyl nitrogen atoms to other metal centers above/below the plane defined by phosphorus and gold atoms. We also showed that the Au 2 Cu 2 clusters 2 and 3 with butterfly- and planar-shaped metal cores (Scheme ) can be formed from 1 (OTf) 2 by coordination of the pyridine nitrogen atoms to the copper­(I) centers on the same side or opposite sides of the phosphorus atoms plane, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline 1–5 exhibit broad and unstructured emission bands peaking at 480, 481, 461, 477, and 462 nm, respectively, which are blue-shifted by 36–54 nm relative to that in the solution state, as a result of the rigid matrix. , When the crystalline sample is being ground into the powder sample, a red-shifted emission is observed in ground 1–5 , with maxima at 510, 502, 498, 501, and 501 nm, respectively. Luminescence mechanochromism of 1–5 can be due to distortions of the excited states and, substantially, is very similar to the so-called luminescence rigidochromism that is caused by the rigidity of the environment surrounding the molecules. Mechanochromic luminescence here is caused by a reduced structural rigidity of the molecules in the excited state caused by grinding-triggered disruption of intramolecular “pyridyl/phenyl” π···π interactions, resulting in a decrease in the energy level of the emissive excited state and a red-shifted emission. Upon exposure of the ground sample to CH 2 Cl 2 vapor, a cyan emission is observed again in reverted 1–5 with maxima at 476, 483, 470, 469, and 464 nm, respectively, as a result of the restoration of π···π interactions between the pyridyl and phenyl rings under CH 2 Cl 2 vapor, which is slightly different from the cyan one in the crystalline sample, possibly attributable to the destruction of partial intermolecular interactions by grinding.…”
Section: Resultsmentioning
confidence: 98%
“…Solid-state emission maxima of 1 – 3 are blue-shifted in comparison to those of solution-phase samples (Table ). This blue shift is an occurrence of rigidochromism, which results from the emission from nonrelaxed excited states in rigid environments, whereas fluid surroundings enable emission from vibrationally relaxed states. Complex 4 behaves in the opposite manner; its emission maximum is red-shifted at 77 K and in powder samples at 298 K in comparison to that in solution at ambient temperature.…”
mentioning
confidence: 99%